2021
DOI: 10.1007/s40747-021-00303-2
|View full text |Cite
|
Sign up to set email alerts
|

System dynamics mechanism of cross-regional collaborative dispatch of emergency supplies based on multi-agent game

Abstract: The cross-regional coordinated dispatch of emergency supplies is a complex issue involving multiple topics, which covers multiple relationships and is affected by multiple variables. In the face of severe emergencies, relief supplies inside a specific area are far from meeting the explosive demand for emergency supplies. Besides, the supply of emergency materials and the disaster areas often have a spatial mismatch. Considering the attributes of externalities and public goods of emergency rescue, there are man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…is often applied to study complex systems and analyze evolutionary trends (53)(54)(55). Some authors recently used system dynamics to simulate and analyze evolutionary game problems (56)(57)(58). In this study, SD was incorporated into the study of the omnichannel feedback mechanism of elderly people to clearly depict the complex relationships and mechanisms of interaction among the subjects.…”
Section: System Dynamics Model Constructionmentioning
confidence: 99%
“…is often applied to study complex systems and analyze evolutionary trends (53)(54)(55). Some authors recently used system dynamics to simulate and analyze evolutionary game problems (56)(57)(58). In this study, SD was incorporated into the study of the omnichannel feedback mechanism of elderly people to clearly depict the complex relationships and mechanisms of interaction among the subjects.…”
Section: System Dynamics Model Constructionmentioning
confidence: 99%
“…Cross‐regional cooperation not only exists to implement emergency reinforcement for the neighboring government but also to deal with the fluidity and extensiveness of crises (J. Liu et al, 2022). Simulation analyses showed that cross‐regional cooperation is conducive to resource mobilization and transportation, thus improving the effectiveness of crisis response (Lv et al, 2018; Qiu et al, 2021; Shao et al, 2018; A. Wang et al, 2021). In practice, cooperation frameworks and agreements are employed to instructed localities to better understand and respect each other's roles and responsibilities when formulating collaborative emergency management plans (Mcguire & Silvia, 2010).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…For instance, Boin et al [12] and Mehrtash et al [13] discussed the importance of crossregional coordination mechanisms through cost-beneft analysis under sudden cross-regional disasters. Pescaroli et al [14] and Qiu et al [15] put forward suggestions on how to construct emergency rescue synergistic processes. Urrutia et al [16] used generalized network autoregressive to interdict potential higher infection areas.…”
Section: Introductionmentioning
confidence: 99%